Dampak Implementasi PSAK 71 terhadap Kualitas Laporan Keuangan Perbankan di Indonesia - Mutiara Damayanti; Yusnaini Yusnaini (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The implementation of PSAK 71 (IFRS 9) in Indonesia marks a crucial paradigm shift from the incurred loss model toward a transparent, forward-looking Expected Credit Loss (ECL) framework. Despite its benefits, this standard poses significant technological integration obstacles and potential agency issues due to technical complexity and managerial subjectivity in loss estimation. This study conducts a Systematic Literature Review (SLR) following PRISMA criteria, examining 30 articles published between 2020 and 2026 to determine success factors and ethical impediments. Mapping results show that 51.6% of literature comes from international publications, with 48.4% focusing on Indonesia, highlighting inadequacies in IT infrastructure and human resources. Findings suggest that while the standard increases value relevance and transparency, its principle-based nature provides discretionary space for forward-looking assumptions that may be exploited for earnings management practices. Through stakeholder and legitimacy theories, the research explains how banking institutions might engage in symbolic compliance to maintain financial images despite internal information asymmetry. Ultimately, the success of PSAK 71 in preserving public interest relies heavily on transforming IT systems into substantial internal control instruments that eliminate "black box" phenomena in banking financial reporting, ensuring long-term accountability and stability.